PENGEMBANGAN MODEL DIKLAT GURU SOSIOLOGI SMA TENTANG STRATEGI PEMBELAJARAN DISCOVERY-INQUIRY BERBANTUAN CD INTERAKTIF - Setyani Budi Rahayu (Universitas Kristen Satya Wacana, 2016)
This research development aimed to develop an education and training model for sociology teachers about inquiry discovery learning aided CD interactive. The steps taken were recognized the potential and problems, formulating design, construct an education and training model and the toolkits, experts test and product revison. Data collection used interview and study of document. The results of this research development indicated that the planning which was done before the education and training begun was to determine the training needs by analyzing the needs of the organization, set the goal of training, composed training programs; composed preliminary and final assessment tools, composed the criteria for successful training. The implementation of education and training development model of high school teachers about learning sociology with inquiry discovery learning aided interactive CD emphasized on training to compose lesson plans and to make CD interactive learning. Monitoring and evaluation for quality assessment needed to be done by the trainees by filling the questionnaire so that the responds toward the accomplishment of training and interviewees could be known. Whereas the evaluation of the traineescould be done through tests and assignments given about making lesson plans and CD interactive learning.